Effects of the Communities that Heal (CTH) intervention on perceived opioid-related community stigma in the HEALing Communities Study: results of a multi-site, community-level, cluster-randomized trialResearch in context - Alissa Davis; Hannah K. Knudsen; Daniel M. Walker; Deborah Chassler; Karsten Lunze; Philip M. Westgate; Emmanuel Oga; Sandra Rodriguez; Sylvia Tan; JaNae Holloway; Sharon L. Walsh; Carrie B. Oser; et al. (Elsevier, 2024)
Summary: Background: Community stigma against people with opioid use disorder (OUD) and intervention stigma (e.g., toward naloxone) exacerbate the opioid overdose crisis. We examined the effects of the Communities that HEAL (CTH) intervention on perceived opioid-related community stigma by stakeholders in the HEALing Communities Study (HCS). Methods: We collected three surveys from community coalition members in 66 communities across four states participating in HCS. Communities were randomized into Intervention (Wave 1) or Wait-list Control (Wave 2) arms. We conducted multilevel linear mixed models to compare changes in primary outcomes of community stigma toward people treated for OUD, naloxone, and medication for opioid use disorder (MOUD) by arm from time 1 (before the start of the intervention) to time 3 (end of the intervention period in the Intervention arm). Findings: Intervention stakeholders reported a larger decrease in perceived community stigma toward people treated for OUD (adjusted mean change (AMC) −3.20 [95% C.I. −4.43, −1.98]) and toward MOUD (AMC −0.33 [95% C.I. −0.56, −0.09]) than stakeholders in Wait-list Control communities (AMC −0.18 [95% C.I. −1.38, 1.02], p = 0.0007 and AMC 0.11 [95% C.I. −0.09, 0.31], p = 0.0066). The relationship between intervention status and change in stigma toward MOUD was moderated by rural-urban status (urban AMC −0.59 [95% CI, −0.87, −0.32], rural AMC not sig.) and state. The difference in stigma toward naloxone between Intervention and Wait-list Control stakeholders was not statistically significant (p = 0.18). Interpretation: The CTH intervention decreased stakeholder perceptions of community stigma toward people treated for OUD and stigma toward MOUD. Implementing the CTH intervention in other communities could decrease OUD stigma across diverse settings nationally. Funding: US National Institute on Drug Abuse.